Analisis Pengaruh Brand Image dan Kualitas Pelayanan terhadap Kepuasan Konsumen melalui Sikap Konsumen - Abd Koder; Amirullah Amirullah (ProBisnis : Jurnal Manajemen, 2026)
This study aims to examine the direct and indirect effects of brand image and service quality on customer satisfaction, with customer attitude as a mediating variable at Kedai Tawa Senja. The research employed a quantitative approach with an explanatory design. The population consisted of all customers of Kedai Tawa Senja, with a sample of 40 respondents selected using purposive sampling. Primary data were collected through a five-point Likert scale questionnaire, while secondary data were obtained from documentation and other relevant sources. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS version 4.0, including evaluation of the measurement model (outer model) and structural model (inner model), as well as hypothesis testing. The results indicate that brand image and service quality have a positive and significant effect on both customer satisfaction and customer attitude. However, customer attitude does not significantly affect customer satisfaction and does not mediate the relationship between brand image and service quality on customer satisfaction. These findings contribute empirically to consumer behavior models, suggesting that in the context of local culinary retail businesses, customer satisfaction is more strongly influenced by direct evaluations of brand attributes and service quality rather than by attitudinal mediation mechanisms.